Tracer Study: The Alignment Of Work Types With The Origin Of Alumni Specialization Of FKM UI - Rina Efiyanna; Sutanto Priyo Hastono; Ahmad Syafiq (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
The purpose of the study is to find out the alignment of the work types with the original specialization of alumni from the public health faculty of Universitas Indonesia based on the results of 2010-2017 tracer study of public health undergraduate of FKM UI. The study used secondary data from the 2010-2017 FKM UI Tracer Study with samples 298 people. Moreover, the study used Multivariate Analysis, especially multiple logistic regression analysis. The results of the multivariate analysis showed that the variables were significantly related to work alignment, namely variables of the origin specialization and the number of applying for jobs. Then, the variables of residency, work waiting period, additional courses and the number of interview calls are called confounding variables. The analysis results of Odds Ratio (OR) from the original specialization variables are 3. It means 3 alumni whose original specialization in Occupational Safety Health (K3) will get job which is line with their specialization 3 times higher than alumni whose specialization in Science Public Health (IKM) after getting controlled variables, such as the number of job applications, residency, work waiting period, additional courses and number of interview calls.